2018
DOI: 10.3390/ijerph15081701
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Hypertension-Related Knowledge and Behavior and Their Associations with Socioeconomic Status among Recently Urbanized Residents in China: 2013–2016

Abstract: The rapid urbanization in China has brought with it some health benefits, but it also brought about a negative influence on the lifestyle of residents. We conducted this study to assess the change in hypertension-related knowledge and behavior from 2013 to 2016 among recently urbanized residents and determine their association with socioeconomic status (SES). This research used data from two cross-sectional studies conducted in Hezuo community in Chengdu, Sichuan province of China. A total of 2268 and 2601 ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…This study found that being unemployed or retired is significantly associated with greater hypertension awareness and treatment. This is consistent with a previous study from China [36], which found that unemployed and retired respondents had higher odds of hypertension related behavior than employed workers. Employment is always thought to have a positive impact on health but unemployment is not always harmful.…”
Section: Plos Onesupporting
confidence: 93%
See 1 more Smart Citation
“…This study found that being unemployed or retired is significantly associated with greater hypertension awareness and treatment. This is consistent with a previous study from China [36], which found that unemployed and retired respondents had higher odds of hypertension related behavior than employed workers. Employment is always thought to have a positive impact on health but unemployment is not always harmful.…”
Section: Plos Onesupporting
confidence: 93%
“…It may lead to poorer access to care, lack of knowledge and awareness of the consequence of uncontrolled hypertension. Similarly, a recent study from China found that the higher educated respondents were more likely to have adequate hypertension related knowledge and behavior to enable them to access, evaluate, utilize and obtain important health knowledge [36]. Well-educated respondents were more likely to adopt health behavior based changes easily and have better resources to improve health behavior including a better social support.…”
Section: Plos Onementioning
confidence: 93%
“…This was inconsistent with previous studies reporting a positive influence of knowledge about hypertension on blood pressure control [ 24 , 43 ]. A lack of association between hypertension knowledge and self-care behaviour has previously been observed in China’s urban residents, indicating that knowledge may be a better predictor for treatment adherence in hypertensive patients but not for preventive measures in the general community [ 22 , 23 ]. These differences highlighted that different approaches should be considered when developing and executing blood pressure control programs depending on the goal of prevention or treatment of hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…These six factors can be modified by sociodemographic variables (such as age, sex, level of education) or psychological characteristics (such as personality), while cue to action can modify health behaviours. In the present study, self-efficacy and hypertension knowledge were included in the model based on its known association with the adoption of hypertension self-care behaviour [15,17,[22][23][24][25][26][27]. Out of these six factors, perceived susceptibility was found to be the weakest predictor of behaviour and had close to no relationship with positive health behaviour [28].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, certain psychological aspects such as the influence of the negative stereotypes associated with age may be related to attitudes toward retirement [78] and have an impact on some older workers' ability to save. In the same vein, due to the strong connection between health and wealth, financial planning for retirement should be considered in its relationship with health planning for retirement [79, 80, 81, 82]. All this should be considered, without forgetting the relevance of similar studies with larger samples and more countries that enrich and advance the study of FPR.…”
Section: Discussionmentioning
confidence: 99%